Wireless telemedicine services as part of an integrated system for e-medicine - CHorbev, Ivan; Madzarov, GJorgji; Mihajlov, Dragan (IEEE, 2008)
This paper presents an overview of the wireless telemedicine components of an integrated system for e-medicine that we propose and implement in the Republic of Macedonia. The introduction of new wireless broadband technologies enabled creation of telemedicine services previously only possible via cable connections. WiMAX and Wi-Fi are the wireless technologies used to implement our telemedicine functionalities. They are shortly described and a number of proposed and provided services are explained. Advanced web programming technologies have been extensively used in implementation of the services. Guidelines are given for further development and implementation. The experience gained draws conclusions that can be used in areas or countries with similar natural or economical conditions.